2009
DOI: 10.4103/0973-1075.58457
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to assess the awareness of palliative care between urban and rural areas of Ernakulum district, Kerala, India

Abstract: Aim:To assess the knowledge and attitude toward palliative care among people residing in urban and rural areas.Materials and Methods:This cross-sectional study was conducted among 185 urban and 165 rural households. Senior-most member of the household present was interviewed using a questionnaire. Only those people who have heard about palliative care were included in the study.Results:Out of 350 people, 47 (13.4%) have heard about palliative care. Of these 38 (20.5%) belonged to urban and 9 (5.4%) belonged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…[14] The aim of palliative care is to get the highest quality of life for patient and their families. [16] As expressed by the 78% of the responders of a community study,[3] home care improves the quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] The aim of palliative care is to get the highest quality of life for patient and their families. [16] As expressed by the 78% of the responders of a community study,[3] home care improves the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[1] National policy is to promote the concept of “ageing in place or aging in own home and home care services and consider institutional care as the last resort.”[2] Some studies found out that palliative home care is better than hospital and also more cost-effective. [3]…”
Section: Introductionmentioning
confidence: 99%
“…A study in Canada showed the consistency and depth of palliative care service provision in British Columbia differed across community sites [7]. In India, the awareness of palliative care was known to be higher in urban areas than in rural areas [8]. The issue of urban-rural disparity thus deserves investigation in the development of palliative care worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…(Rajagopal & Palat, 2002) Homebased palliative care are preferred widely and thus mandates the need for wider practice. (Joseph, Jayarama, & Kotian, 2009)Recruitment of volunteers is essential for meeting the man power requirements in developing economies. Volunteers have the potential to cover wider area in community education and health care.…”
Section: Introductionmentioning
confidence: 99%